Can ESG investments and new environmental law improve social happiness in China? - Lu, Peiyao; Hamori, Shigeyuki; Tian, Shuairu (Frontiers in Environmental Science, 2023)
Air pollution was a serious issue in China in the early 2010s, threatening public health and sustainable economic development. The Chinese government established a new environmental protection law in 2015 in order to address air pollution and other environmental issues. This paper investigates the impact of the new environmental law and ESG investments on air pollution and social happiness. We discovered that the implementation of the new environmental law and ESG investments significantly improved social happiness by reducing air pollution. One unit increase in ESG investments would result in a 0.334 unit decrease in air pollution and 0.225 unit increase in social happiness.